WRITTEN ANALYSIS ON LOCAL FACEBOOK HOUSING ADVERTISEMENT - robi kurniawan; harum natasha (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This study explores a written analysis on Facebook closed group housing advertisements of Central Michigan University (CMU) by formulating generic structure as well as identifying the language features. The generic structure is formulated by applying Swales’ moves and steps, while language features (tenses, pronouns, and lexical items) were analyzed by using AntConc software (Anthony, 2014). Generic structures show consistent moves and steps, while analysis on language features reveals that the advertisements are mostly composed in present tense, the pronoun “you” justifies the readers as the audience (30 appearances), and “looking” is the language feature of the set intention. Furthermore, the analysis on generic structures indicates that there are three moves which are consistently employed by the author: set intention with two steps (number and desired occupants), description of the place with three steps (location, cost, and selling points), and invitation to respond with two steps (imperatives and means to communicate). In addition, it is found that each posting is relatively brief with an average of only 96.5 words, 7.7 sentences, and 1.7 sentence fragments. Fragments make up 22% of total 77 sentences. Although this study has clearly generated valuable findings related to generic structure and language feature, it is still potential to be developed and applied in academic writing setting.